Decellularized ECM Effects on Human Mesenchymal Stem Cell Stemness and Differentiation - Pattabhi, Sudhakara rao (Differentiation, 2015)
Microenvironment extracellular matrices (ECMs) influence cell adhesion, proliferation and differentiation. The ECMs of different microenvironments have distinctive compositions and architectures. This investigation addresses effects ECMs deposited by a variety of cell types and decellularized with a cold-EDTA protocol have on multipotent human mesenchymal stromal/stem cell (hMSC) behavior and differentiation. The cold-EDTA protocol removes intact cells from ECM, with minimal ECM damage and contamination. The decellularized ECMs deposited by cultured hMSCs, osteogenic hMSCs, and two smooth muscle cell (SMC) lines were tested for distinctive effects on the behavior and differentiation of early passage (‘naïve’) hMSC plated and cultured on the decellularized ECMs. Uninduced hMSC decellularized ECM enhanced naïve hMSC proliferation and cell motility while maintaining stemness. Decellularized ECM deposited by osteogenic hMSCs early in the differentiation process stimulated naïve hMSCs osteogenesis and substrate biomineralization in the absence of added dexamethasone, but this osteogenic induction potential was lower in ECMs decellularized later in the osteogenic hMSC differentiation process. Decellularized ECMs deposited by two smooth muscle cell lines induced naïve hMSCs to become smooth muscle cell-like with distinctive phenotypic characteristics of contractile and synthetic smooth muscle cells. This investigation demonstrates a useful approach for obtaining functional cell-deposited ECM and highlights the importance of ECM specificity in influencing stem cell behavior.